PERLINDUNGAN HUKUM TERHADAP JAMINAN KESEHATAN TENAGA KERJA PADA PT. SINAR REKSA KENCANA DI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Yella Andriani; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Health Insurance is a guarantee that givinghealth protection to the member who has been paying due or the dues are paid by the government. It means the employees have to protect by using legal protection. The objectives of this research are to find out the form of legal protection toward the the Sinar Reksa Kencana. Inc. employees’ at Peranap Indragiri Hulu Regency.To find out the problems of legal protection implementation toward the the Sinar Reksa Kencana.Inc. employees’ at Peranap Indragiri Hulu Regency. To find out the efforts that doing by Sinar Reksa Kencana.Inc. in legal protection toward the Sinar Reksa Kencana.Inc.employees’ healthyat Peranap Indragiri Hulu Regency.This research issociological research. The researcher makes a direct research to find out the complete data about these problems. This research is located at Peranap Indragiri Hulu Regency. The population and the samples are all the employees. The techniques of collecting data that using by the researcher areinterview, questionnaire and literature study. The legal protection toward the health insurance at Sinar Reksa Kencana. Inc. employees’ at Peranap Indragiri Hulu Regency is not runwell, because there are many problems are found toward health insurance at Sinar Reksa Kencana. Inc. employees’ at Peranap Indragiri Hulu Regency such as, the company does not known about employees right, the employees educations are low, there is no trade union at the Sinar Reksa Kenaca. Inc. The efforts to solve this problems are increasing the knowledge of the company toward employees right, increasing the education of the employees and creating the trade union at the Sinar Reksa Kencana. IncKey Word: Legal Protection – Health Insurance - Employee